Just Another Link in the Chain? Delegation, Agency Theory and National Parliaments in EU Affairs - Auel, K (Connex Report Series, 2008)
"Meaning and Practice of Accountability in the EU Multi-Level Context" (ed. Deirdre Curtin and Anchrit Wille) Agency theory has been used to model representation in parliamentary systems as a single chain of delegation, which has now been extended to the European level. In the literature the debate whether national parliaments have, as a result, become the weakest link in this chain is ongoing. On the basis of a modified delegation model, which acknowledges the neglected distinction between parliamentary majority and opposition and unpacks the concept of parliamentary scrutiny as an instrument to contain agency loss, the paper proposes a new framework for the assessment of their respective roles in EU politics. The article is mainly theoretical is its aim, but comparative case studies of the Folketing, the Bundestag and the House of Commons provide an illustration.